Non-perennial rivers and streams in extreme hydrological conditions—comparing the effectiveness of amplicon sequencing and digital microscopy for diatom biodiversity appraisal - Burfeid-Castellanos, Andrea M.; Mones, Phillip; Dani, Mimoza; Beszteri, Bánk (Frontiers in Ecology and Evolution, 2024)
Non-perennial rivers and streams are increasingly present, in part because of climate change, even in the temperate climate. However, how the loss of connectivity and complete drying affects microphytobenthos in general and diatom communities in particular has gone mostly unstudied. With this paper we aim to close this gap, identifying diatom biodiversity through manual digital microscopy and rbcL amplicon sequencing, to observe a) which method is better suited to it and b) how the ecotone flow-pool-dry affects diatom diversity under duress. Three karstic, non-perennial rivers and streams with a gradient from natural to anthropogenically disturbed were sampled under flooding conditions and after a long and intense drought in 2022. Our results show that digital microscopy shows a higher diversity and species richness than amplicon sequencing. We posit that this might be due to a reduced pool of sub-aerophile taxa having been sequenced and being part of the reference database. Furthermore, the effect of drying only resulted in a reduction in diversity after this drought, although the biofilm was still alive under these conditions. To use amplicon sequencing for non-perennial river diatom diversity monitoring, the reference databases will have to be adapted to such systems, as most rivers may be subjected to drying regularly in the future.